Designing of a Single Pack Wash Primer for Aluminum Surfaces in a Marine Environment - Pillai, A. G. Gopalakrishna (Fishery Technology, 1971)
Design aspects and comparative performances of different laboratory formulations of wash primers were studied under laboratory and field! conditions with reference to scratch hardness. flexibility, stability, resistance to corrosion and adhesiveness. The different formulations of single pack wash primers tested have shown superiority of the formulation prepared out of "mowital" and that it is comparable in performance to double pack wash primer.